Pembuatan Keripik Pisang Lumer dalam Pengembangan Usaha Mikro dengan Pemanfaatan Sumber Daya Di Desa Sri Menanti - Sukawati Sukawati; Moh Habibul Mujtaba; Rosa Kamelia Sari; Siti Afifah; Sindi Rosadi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Sri Menanti Village has significant potential in the agricultural sector, particularly in banana production. However, the economic value of bananas is often underutilized due to limited innovation in processing. This study aims to develop micro-enterprises through the production of an innovative product called keripik pisang lumer (melt-in-the-mouth banana chips). The method used is a participatory approach involving local communities in training, production, and marketing. The results show that utilizing local resources can increase product value and open up new business opportunities. Keripik pisang lumer has become a popular snack alternative with strong potential for both local and regional markets